Animal coloration research: why it matters. (22nd May 2017) - Caro, Tim; Stoddard, Mary Caswell; Stuart-Fox, Devi
Abstract : While basic research on animal coloration is the theme of this special edition, here we highlight its applied significance for industry, innovation and society. Both the nanophotonic structures producing stunning optical effects and the colour perception mechanisms in animals are extremely diverse, having been honed over millions of years of evolution for many different purposes. Consequently, there is a wealth of opportunity for biomimetic and bioinspired applications of animal coloration research, spanning colour production, perception and function. Fundamental research on the production and perception of animal coloration is contributing to breakthroughs in the design of new materials (cosmetics, textiles, paints, optical coatings, security labels) and new technologies (cameras, sensors, optical devices, robots, biomedical implants). In addition, discoveries about the function of animal colour are influencing sport, fashion, the military and conservation. Understanding and applying knowledge of animal coloration is now a multidisciplinary exercise. Our goal here is to provide a catalyst for new ideas and collaborations between biologists studying animal coloration and researchers in other disciplines. This article is part of the themed issue 'Animal coloration: production, perception, function and application'.